(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Great importance is paid to the physical development of school children, the positive influence of physical culture for the growth and development of children has been proven. At the same time, indicators in sports schools are falling due to insufficient development of physical qualities. The problem requires studying and improving the training process of athletes. The aim of the study: To increase the effectiveness of the training process of athletes aged 9-11 years due to the development of certain motor qualities. Study design: Pedagogical experiment. Research methods: The pedagogical experiment was conducted on the basis of the Olympic Reserve School number 1 (Kirov, Russia) from August to November 2022. The study involved children aged 9-11 years. 2 groups were formed: experimental and control consisting of 25 boys each. Classes were held 3 times a week. Children from the control group were engaged in the usual program, and children from the experimental group performed exercises to develop physical qualities. The complex was used for 10 weeks. Tests that were used in the study: Long jump from a place, Shuttle run 3 x 10m, Squats for 30 seconds, Hand strength, Leaning forward from a sitting position. Results: After the study, the experimental group was ahead of the control group in almost all indicators. In the long jump test, the difference between the experimental and control groups was 2.3cm (P<0.05). In the test, the shuttle run is 3x10m, the difference is 0.5 sec (P<0.05). In the “Squat for 30 seconds” test, the difference is 1.6 squats (P<0.05). In the test, the brush strength is 2 kg difference (P<0.05). There is no difference in the forward tilt test at the end of the experiment (P>0.05). Comparison of the results of the children of the control and experimental groups at the end of the pedagogical experiment indicates the superiority of the children of the experimental group. Thus, analyzing the results of testing the physical fitness of athletes aged 9-11, we can talk about the positive impact of the methodology proposed during the pedagogical experiment for the development of physical qualities of younger athletes. Conclusion: If a set of exercises aimed at developing physical qualities is purposefully applied in sports schools in working with children aged 9-11 years, then the indicators of children will improve significantly. This will increase the efficiency of the training process. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 246-253